The Reciprocal Effect of Elevated CO2 and Drought on Wheat-Aphid Interaction System - Xie, Haicui; Shi, Fengyu; Li, Jingshi; Yu, Miaomiao; Yang, Xuetao; Li, Yun; Fan, Jia (Frontiers in Plant Science, 2022)
Due to rising concentration of atmospheric CO2, climate change is predicted to intensify episodes of drought, however, our understanding of how combined environmental conditions, such as elevated CO2 and drought will influence crop-insect interactions is limited. In the present study, the direct effects of combined elevated CO2 and drought stress on wheat (Triticum aestivum) nutritional quality and insect resistance, and the indirect effects on the grain aphid (Sitobion miscanthi) performance were investigated. The results showed that, in wheat, elevated CO2 alleviated low water content caused by drought stress. Both elevated CO2 and drought promoted soluble sugar accumulation. However, opposite effects decreased by elevated CO2 and increased by drought were found on the amino acid content. Further, elevated CO2 down-regulated the jasmonic acid (JA) -dependent defense, but up-regulated the salicylic acid (SA)-dependent defense. Meanwhile, drought enhanced abscisic acid accumulation that promoted the JA-dependent defense. For aphid, its feeding always induced phytohormone resistance in wheat under either elevated CO2 or drought condition. And similar aphid performance between control and the combined two factors were observed. We concluded that, the aphid damage suffered by wheat in the future under combined elevated CO2 and drier conditions tends to maintain status quo. We further revealed the mechanism by which it happened from the aspects of wheat water content, nutrition and resistant to aphid.